2017
DOI: 10.1002/jso.24674
|View full text |Cite
|
Sign up to set email alerts
|

Variation in use of postoperative chemoradiation following surgery for T1 and T2 oropharyngeal squamous cell carcinoma; National Cancer Database

Abstract: Background and Objectives Primary surgical treatment of patients with early T-classification (T1-T2) oropharyngeal squamous cell carcinoma (OPSCC) has increased. We sought to determine how often these patients receive postoperative chemoradiation (CRT). Methods Patients with T1-T2 OPSCC in the National Cancer Database who underwent primary surgery were evaluated for receipt of postoperative CRT. Postoperative CRT use was examined among patients with high risk factors (positive margins and/or extracapsular sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Disparities in HPV testing may reflect differences in access to pathologists and pathology departments that perform the test. It has been shown that guideline changes are slowly adopted in the field of head and neck and thyroid cancer 17,18 . In addition, HPV testing can be expensive and the various methodologies are not yet standardized 17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in HPV testing may reflect differences in access to pathologists and pathology departments that perform the test. It has been shown that guideline changes are slowly adopted in the field of head and neck and thyroid cancer 17,18 . In addition, HPV testing can be expensive and the various methodologies are not yet standardized 17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of positive resection margins, chemotherapy should be applied in accordance with recent guidelines. [9,10] In this study, all patients receiving chemotherapy were excluded (Fig 1). Thus, we do not expect a serious bias due to positive resection margins.…”
Section: Limitationsmentioning
confidence: 99%
“…[8] Regarding the question of PORT in T1/2 HNC, the NCCN guidelines provide the following recommendation in relation to risk profile: Adjuvant irradiation should be used in patients with oropharynx and hypopharynx cancer and a pN0 or N1 situation as soon as multiple minor risk factors-e.g., perineural invasion, lymphovascular space invasion or close margins (< 5 mm)-appear. [9,10] If an extranodal extension (ECE) and/or positive resection margins occur, adjuvant chemoradiotherapy is recommended. [9][10][11] In patients with oral cavity cancer and a N1 situation, adjuvant irradiation should be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Nevertheless, it is debatable for patients with locally circumscribed primaries (pT1-pT2) with a single ipsilateral lymph node metastasis (pN1) and without the previously mentioned adverse features. 6,8 One reason is that no results of prospective randomized trials addressing this topic are available. Only a few retrospective studies [9][10][11][12][13][14] provide data upon which therapeutic recommendations and rational clinical decision making can be based.…”
Section: Introductionmentioning
confidence: 99%